Анализ критериев оценки эффективности функционирования маршрутных систем городов - Акбар, Джан Полад (НТУ "ХПИ", 2015)
Проведен аналитический обзор существующих критериев оценки эффективности функционирования пассажирских маршрутных систем городов. Выявлены проблемы транспортного обслуживания населения города Кабул и представлены пути их решения. Предложен подход к формированию оценочного критерия, который учитывает интересы заказчиков услуг по транспортному обслуживанию в городах. Результаты исследования могут быть использованы при проведении мероприятий по усовершенствованию существующих городских пассажирских маршрутных систем, а также при разработке новых их вариантов.

The article deals with the study to substantiate and select the criteria for evaluating the performance of urban mass transit. The basic result of the study is the option criterion for evaluating the performance of urban passenger route network that takes into account the peculiarities of transport service in the city of Kabul of the Islamic State. The scientific breakthrough of the research is to develop an approach to make the evaluation criteria that consists of the following major stages: selection of the target segment; determination of the partial performance criteria for each customer; presentation of the general performance criterion. The practical significance of the research results is the possibility of using the approach developed to make the criteria for evaluating the efficiency of existing and development of new route passenger transportation systems.
Analysis of criteria to evaluate the performance of urban route systems
Keywords: городской пассажирский транспорт; критерий эффективности; затраты пассажиров; пассажиропотоки; urban mass transit; urban route systems; efficiency; passengers' travel cost